The Role of Second Metal on the Catalytic in-Situ Generation of H2O2 by Fe/Ni Bimetallic Nanoparticles: Degradation Studies of Metronidazole Antibiotic - Yildiz, Burcin; Sener, Ecehan; Hanay, Ozge (Jihad Daneshgahi, 2024)
Fe-based bimetallic particles have been shown potential for Fenton process but the investigation of a second metal role on bimetallic particles remains challenging. In this study, nano sized Fe/Ni (nFe/Ni) particles were synthesized at different Ni loading rates (1, 3.5, 10 wt%) and used as catalyst for in-situ generation of H2O2 by activating dissolved oxygen. Fenton process efficiency was defined via the degradation of a model organic pollutant as metronidazole (MNZ) antibiotic under different operational parameters. The experimental results indicate that the addition of Ni to nZVI particles with high loading significantly increased the production of H2O2, while low Ni loading rate resulted in high MNZ removal efficiency. The maximum removal efficiency of MNZ was about 99% obtained for 0.1 g/L nFe/Ni synthesized at 1% Ni loading rate at pH:3 within 1 h. At pH:7, the MNZ removal was entirely due to adsorption, which was dependent on the catalyst dosage. In addition, the potential degradation products of MNZ were suggested based on the intermediates detected by LC-MS/MS. The conversion of MNZ to low and different molar mass intermediates confirmed the different degrees of MNZ degradation.
Keywords: Heterogeneous Fenton; In-situ H2O2; Metronidazole; Nano Fe/Ni; Ni loading